Analysis of The Heavy Metal Cd Content in Ricefield Eel from Rawa Taliwang Lake, West Sumbawa Regency - Khairuddin; M. Yamin; Kusmiyati (Postgraduate, University of Mataram, 2024)
It is important to carry out research on heavy metal in fish body. The specific aims and targets of this research are: Want to know the metal content of Cadmium (Cd) in Ricefield eels (Monopterus albus) which comes from Rawa Taliwang Lake. The specific benefit is to protect consumers who consume fish from heavy metal contamination. The research was carried out at Rawa Taliwang Lake, namely in an area that is submerged in water. There are 2 research stations, namely in the eastern and western parts of the lake. Data collection method was carried out using traps (Bubu). Four Ricefield eel samples were taken at each station. Next, the rice eel samples were put into a plastic bag and then stored in a sample box. The research samples were then analyzed at the Mataram Uviversity analytical laboratory and at Environmental Laboratory of the Environmental and forestry services West Nusa Tenggara Province. The data analysis method is carried out by taking the tissues from the Ricefield eel muscles, and then analyzed for Cd heavy metal content by using Atomic Absorption Spectrophotometer. Measurement of heavy metals in Ricefield eel tissue was carried out by adding concentrated HNO3 and HClO4 , heated at a temperature of 60-70ºC for 2-3 hours until the solution was clear. Samples are ready to be measured with AAS using an air-acetylene flame. The conclusion of this research is that the content of Cd heavy metal in Ricefield Eels (Monopterus albus) originating from Rawa Taliwang Lake ranges from 2.55 - 4.01 mg/kg (ppm).